Literature Study of the Role of Technology in Education - Siahaan, Jesica Aime; Siregar, Sakinah Salsabila; Pane, Raudahtul Jannah (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
This literature study explores the multifaceted role of technology in education. With the rapid advancement of digital technology, its integration into educational settings has become increasingly prevalent, reshaping teaching and learning practices worldwide. Through an extensive review of academic literature, this study examines various dimensions of technology's role in education, including its impact on pedagogy, student engagement, learning outcomes, and educational equity. The research synthesizes empirical evidence and theoretical frameworks to elucidate the potential benefits and challenges associated with technology integration in diverse educational contexts. Furthermore, the study investigates emerging trends such as online learning platforms, educational software applications, immersive technologies (e.g., virtual reality, augmented reality), and adaptive learning systems, highlighting their potential to enhance instructional delivery and personalize learning experiences. Additionally, the research discusses the importance of digital literacy and teacher professional development in leveraging technology effectively for educational purposes. Moreover, the study addresses critical issues such as digital divide, privacy concerns, and ethical implications associated with technology use in education. By analyzing the current state of research and identifying gaps in knowledge, this study offers insights into future directions for research, policy development, and educational practice in harnessing the transformative potential of technology to improve teaching and learning outcomes. Ultimately, this literature study contributes to a comprehensive understanding of the evolving role of technology in education and provides a foundation for informed decision-making and innovation in educational technology integration efforts.